Афілофороїдні гриби Голосіївського лісу (м. Київ) - Іваненко, О.М. (Український ботанічний журнал, 2011)
На территории Голосеевского леса выявлено 64 вида афиллофороидных грибов, которые относятся к 42 родам, 18 семействам и 7 порядкам. Из них 31 вид является новым для НПП «Голосеевский», 9 видов — для Право бережной Лесостепи Украины. This work presents data of the research on aphyllophoroid fungi in the forest Holosiivsky. Altogether 64 species of wood-destroying fungi from 44 genera, 18 families and 7 orders are recorded. 31 species are found to be new for the National Nature Park «Holosiivsky» and 9 species — for the Right-bank Forest-steppe of Ukraine.